2014
DOI: 10.1186/1475-2875-13-211
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in universal coverage and utilization of insecticide-treated bed nets in migrant plantation workers in Myanmar

Abstract: BackgroundHigh coverage of the bed nets can reduce mortality and morbidity of mosquito-borne diseases including malaria. Although the migrant workers are at high risk of malaria, there are many hidden challenges in universal coverage and utilization of the insecticide-treated nets (ITNs) in this populations.MethodsCross sectional study was conducted in 170 migrant workers in palm oil plantation sites in Tanintharyi Region and 175 in rubber plantation sites in Mon State. A multistage stratified cluster sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 15 publications
6
64
1
Order By: Relevance
“…Despite the very high respondents utilizing LLIN every night in this study, about half reported understanding the bene t of bed net as a prevention tool against malaria. It is not clear what could be driving the low understanding among the community, however, lack of knowledge, perceptions of risk and inadequate social behaviour change communication programme may contributing to the observed pattern (19,20). This study also noted that a small number of respondents stated that they did not use bednets because of low mosquito population density and low disease incidence.…”
Section: Discussionmentioning
confidence: 71%
“…Despite the very high respondents utilizing LLIN every night in this study, about half reported understanding the bene t of bed net as a prevention tool against malaria. It is not clear what could be driving the low understanding among the community, however, lack of knowledge, perceptions of risk and inadequate social behaviour change communication programme may contributing to the observed pattern (19,20). This study also noted that a small number of respondents stated that they did not use bednets because of low mosquito population density and low disease incidence.…”
Section: Discussionmentioning
confidence: 71%
“…Many migrants work in high-risk environments such as natural forest, palm oil or rubber plantations, and fish farms 89. In areas where major epidemiological shifts toward elimination have occurred, these migrant workers, predominantly adult males, sustain transmission 71.…”
Section: High-risk Groupsmentioning
confidence: 99%
“…Myanmar aims at achieving and maintaining 100% access and utilization of ITNs at the household level. Previous studies from Myanmar have assessed ownership and utilization of ITNs in the general population [12], in specific regions/settings [13,14] and key migrant occupations such as plantation workers [15,16]. However, information on ITN usage among underfive children and the associated factors is scarce.…”
Section: Introductionmentioning
confidence: 99%